A Novel Inflammation and Insulin Resistance Related Indicator to Predict the Survival of Patients With Cancer - Ruan, Guo-Tian; Xie, Hai-Lun; Zhang, He-Yang; Liu, Chen-An; Ge, Yi-Zhong; Zhang, Qi; Wang, Zi-Wen; Zhang, Xi; Tang, Meng; Song, Meng-Meng; Zhang, Xiao-Wei; Yang, Ming; et al. (Frontiers in Endocrinology, 2022)
Background: Systemic inflammation and insulin resistance (IR) are closely related in patients with cancer. However, there is no relevant indicator that combines inflammation and IR to predict patient prognosis. Therefore, this study aimed to develop and validate a novel inflammation- and IR-related marker in patients with cancer. Methods: The total cohort of this study included 5221 patients with cancer, and the training and validation cohorts were randomized in a 7:3 ratio. C-reactive protein (CRP) and fasting triglyceride glucose (TyG) were used to reflect patients’ inflammation and IR status, respectively. The CRP-TyG index (CTI) was composed of CRP and TyG. The concordance (C)-index, receiver operator characteristic (ROC) curve, and calibration curve reflected the prognostic predictive power of CTI. Univariate and multivariate survival analyses predicted the prognostic value of CTI in patients with cancer. Results: The C-indices of CTI in patients with cancer were 0.641, 0.638, and 0.651 in the total, training, and validation cohorts, respectively. The 1-, 3-, and 5-year ROC and calibration curves showed that CTI had a good predictive ability of survival in patients with cancer. Meanwhile, patients with high CTI had a worse prognosis compared to patients with low CTI (total cohort: hazard ratio [HR] = 1.57, 95% confidence interval [95% CI] = 1.44–1.72; training cohort: HR = 1.49, 95% CI = 1.34–1.67; validation cohort: HR = 1.82, 95% CI = 1.54–2.15]. Conclusion: The CTI is a useful prognostic indicator of poor prognosis and a promising tool for treatment strategy decision-making in patients with cancer.